2020
DOI: 10.3390/su12156249
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Agricultural Service on Grain Production in China

Abstract: The development of agricultural services was the most important change in China’s agricultural production in the past 20 years. Using nationally representative provincial-level panel data, this study shows that agricultural service has a positive impact on technical efficiency at a significance level of 0.06. Based on this study, if the share of agricultural service cost increases by 1%, technical efficiency will increase by 0.35%. In other words, this study provides an empirical explanation of the positive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Secondly, service collaboration can improve the service quality of agricultural machinery through the specialization of service quality and service means, and then realize the high-quality operation of conservation tillage. In the aspect of service quality specialization, in order to ensure the service quality of agricultural machinery service, the service subjects in the service alliance reach a consensus through service coordination, that is, each subject needs to provide agricultural machinery service in a standardized and high-quality way, so that the implementation of the whole conservation tillage technology system can get professional and high-quality services (Qiao, 2020), and then realize the high-quality operation of conservation tillage technology system. At the same time, in terms of specialization of service means, service alliances will sign full-process service agreements with farmers in the form of alliances through service collaboration (Tang et al, 2018).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Secondly, service collaboration can improve the service quality of agricultural machinery through the specialization of service quality and service means, and then realize the high-quality operation of conservation tillage. In the aspect of service quality specialization, in order to ensure the service quality of agricultural machinery service, the service subjects in the service alliance reach a consensus through service coordination, that is, each subject needs to provide agricultural machinery service in a standardized and high-quality way, so that the implementation of the whole conservation tillage technology system can get professional and high-quality services (Qiao, 2020), and then realize the high-quality operation of conservation tillage technology system. At the same time, in terms of specialization of service means, service alliances will sign full-process service agreements with farmers in the form of alliances through service collaboration (Tang et al, 2018).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Input constraints on the quantity and quality of agricultural labor may lead to extensive farming operations and lagging technology adoption, and ultimately reduce cultivated land productivity. AMS, as an available source of mechanization for smallholders, can reduce labor drudgery and alleviate agricultural labor shortages at a relatively lower cost than hired labor and/or purchased machinery (Tang et al, 2018;Daum and Birner, 2020;Qiao, 2020). As such, the adoption of AMS can reduce or compensate for the loss of cultivated land productivity due to agricultural labor shortages.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A trend towards a gradual shortage of agricultural labor has emerged. Mechanization is an effective labor-saving method, although smallholders have only a limited capacity to acquire and apply machinery as it carries a heavy financial burden and their farms are both small in scale and fragmented (Benin 2015;Adekunle et al, 2016;Qiao 2020;Wang et al, 2020;Mahasuweerachai and Suksawat 2022). In this context, increasing the availability of agricultural machinery may contribute to the viability of smallholder farming and therefore boost cultivated land productivity (Rigg et al, 2016;Takeshima, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, rational small-scale farmers allocate their family's flexible management structure to a limited labour force to maximize benefits. Most of the family labour force tends to increase family income by comparing non-agricultural employment activities, such as migrant workers, with higher income, which reduces the input of the agricultural production labour force and facilitates family income due to the rigid allocation of the labour force [54]. Savary et al [55] evaluated the central Asian regions and found that farmers increase the input of alternative elements to cope with insufficient labour resources in agricultural production.…”
Section: Background Analysis and Hypothesis Developmentmentioning
confidence: 99%